THE EXPANSION OF THE TRANSNATIONAL AND MULTINATIONAL CORPORATIONS IN THE GLOBAL ECONOMY - Paul-Bogdan Zamfir (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2012)
The phenomenon of transnationalisation and multinationalisation evokes just the differences between the two types of corporations. It can be said that a transnational company is above geographical boundaries, wich from the perspective of revolutionary technological communications and transport have been dimmed, but above the borders represented by language, culture, mentalities and technology. The transnational company operates spot transactions because it is listed on the various first rank Stock Exchanges and the financial, technical, image and brand results recorded by this, are public information that it is measuring the success or unsucces of the transnationalisations phenomenon. By comparison, the multinational company is listed either at stock exchanges of secondary importance, or it is a group or family bussines which has the active abroad. At the same time the multinational corporations effectively produce without to generate significant resources for the development of it's own research activities, so, having failed to impose an uniform structure and culture regardless of the assets location. Another significant difference is at the financing access. The transnational company is standing in attention of the rating firms having a low-risk investment that it allows to access the financing at low cost. In most cases, multinational society has limited financial funding in the country of origin, sometimes exclusive relying on the raised funds of the branches which it controls.